Pulsed Plasma-Chemical Modification of SiO2 Nanopowder by ZnxOy Nanoparticles; International Journal of Nanoscience; Vol. 20, iss. 1 - Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna; Ponomarev D. V. Denis Vladimirovich; Zhuravlev M. V. Mikhail Valerievich; Pyatkov I. Igor; Konusov F. V. Fedor Valerievich; Lapteva O. P. Olga Pavlovna; Gadirov R. M. Ruslan Mukhamedzhanovich (2021, 2021)
Title screen